Influência do histórico térmico na morfologia de cristais de parafina e nas características reológicas de óleos parafínicos em baixas temperaturas - Andrade, Diogo Elias da Vinha (2017)
Waxy crude oil is a complex mixture of hydrocarbons consisting of paraffins, aromatics, naphthenes, asphaltenes and resins. At low temperatures the solubility of high molecular weight components in the oil is decreased and especially the n-paraffins tend to precipitate as crystal structures. These crystals provide a non-Newtonian behavior to the fluid, tend to deposit in the inner surface of pipelines and are responsible for the gelation of the oil when the flow is interrupted. In such cases, the pressure needed to restart the oil flow in subsea pipelines can be much larger than the usual steady-state pressure as the temperature in such environment can be as low as 4 °C. The literature has shown that not only the temperature itself but also the fluid shear and thermal histories have significant influence on the yield stress of waxy crude oils. The current work shows the effect of the initial cooling temperature on the waxy crude oil viscosity, gelation temperature and critical stress. It is showed that the initial cooling temperature affects the mechanical behavior of crude oils at low temperature. It is presented that crystallization is the process where an ordered solid structure is formed from a disordered phase. This process involves two main stages, namely nucleation and crystals growth. As paraffins nucleation is a stochastic process, a supercooling is needed to the onset of this phenomenon. In other words precipitation of crystals could not take place at the solidliquid equilibrium thermodynamic temperature, Teq,SL. Therefore, during the cooling, it is required that the fluid reaches a certain temperature, below the Teq,SL, to initiate the nucleation process. This work proposes an experimental procedure to determine consistently the highest solid-liquid thermodynamic equilibrium temperature. By means of rheometric tests, it is showed that the supercooling affects the nucleation rate and the crystals morphology, and also it is influenced by the cooling rate and the initial cooling temperature. One can conclude that the higher the supercooling the higher the number of crystals and, as consequence, the lower the crystals length. Finally, the crystals morphology and the length affect the mechanical properties of the waxy oil.